Modular ultrasonic vibration device for micro electrodischarge machining - Saleh, Tanveer; Mollik, Md Shohag; Islam, Md Saiful (2019)
Micromachining technologies have been in the forefront due to massive demands in many engineering, production and manufacturing sectors. Micro Electric Discharge Machining (μ-EDM) is one of the most commonly used tool based micromachining techniques available to produce microscopic features and components for various industries. However, one of the drawback for μ-EDM is the slow speed of the process. In order to improve the machining performance by reducing the machining time researchers have tried to implement ultrasonic assisted (UA) μ-EDM operation. However, there is no product available in the market that is dedicated for μ-EDM machine to produce ultrasonic vibration. This disclosure attempts to propose a design of such a vibrator that can be used for μ-EDM operation.